2002
DOI: 10.2527/2002.802467x
|View full text |Cite
|
Sign up to set email alerts
|

Arginine catabolism in lactating porcine mammary tissue2

Abstract: In vivo studies have shown that the uptake of plasma arginine by the lactating porcine mammary gland greatly exceeds the output of arginine in milk, but little is known about the metabolic fate of arginine in this organ. The objective of this study was to quantify arginine catabolism via arginase and nitric oxide synthase pathways in the mammary tissue of sows on d 28 of lactation. Mammary tissue slices (approximately 60 mg) were incubated at 37 degrees C for 1 h in 2 mL of Krebs bicarbonate buffer containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 38 publications
2
58
0
Order By: Relevance
“…Supernatants from stimulated PM were used to measure NO production using the Griess reagent method (Molecular Probes). In addition, the extracellular concentration of L-arginine was tested in supernatants by HPLC (Dr. G. Wu, Texas A&M University, College Station, TX) as described previously (21).…”
Section: Cocultures In Transwells (Boyden Chambers)mentioning
confidence: 99%
“…Supernatants from stimulated PM were used to measure NO production using the Griess reagent method (Molecular Probes). In addition, the extracellular concentration of L-arginine was tested in supernatants by HPLC (Dr. G. Wu, Texas A&M University, College Station, TX) as described previously (21).…”
Section: Cocultures In Transwells (Boyden Chambers)mentioning
confidence: 99%
“…TROTTIeR et al (1997) observed that the level of arginine in sow's milk is smaller than the supply of this amino acid to the mammary gland due to its continue degradation by mammary tissue (O'QUINN et al, 2002). In the present study, crude protein or amino acid content of milk, including arginine itself, were not altered by topdressing L-arginine HCL at 1% supplementation, indicating that despite increasing arginine supply in the bloodstream, level of supplementation was not enough to exceed the threshold of arginine degradation in the mammary tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Since arginine is an essential amino acid for young piglets (O'QUINN et al, 2002) and its supplementation in artificially fed neonates improved their development (KIM et al, 2004), it has been speculated about the potential ability to manipulate milk composition with arginine supplementation. TROTTIeR et al (1997) observed that the level of arginine in sow's milk is smaller than the supply of this amino acid to the mammary gland due to its continue degradation by mammary tissue (O'QUINN et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Arginine (Arg) is a versatile amino acid that is used by different tissues in several metabolic functions, including the production of urea, creatinine and other blood biomarkers [11,19,21]. Although the subject is significant in relation to the metabolism of animals, very few studies of the effects of Arg supplementation in horses have been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it contributes to the formation of polyamines, which are important regulators of lactogenesis and protein synthesis for the production of milk [4,11,16,18,19]. In this context, it has been demonstrated that the absorption of Arg by mammary tissue is important for angiogenesis and for the production of other amino acids during the lactation period [19,25]. In most animal species, the presence of Arg in milk is low.…”
Section: Introductionmentioning
confidence: 99%